ASSESSING THE ECONOMIZATION, EFFICIENCY AND EFFECTIVENESS OF HUMAN RESOURCES FUNCTIONS THROUGH MANAGEMENT AUDIT AT PILLAR MAS GROUP - Cholifatul Fitria, Isna; Murnisari, Retno (Universitas Tulungagung, 2024)
This study aims to assess the economy, efficiency, and effectiveness of HR functions and provide recommendations for various issues found at Pilar Mas Group. The HR functions examined include HR planning, HR recruitment, HR selection and placement, HR training and development, career planning and development, employee performance evaluation, compensation and rewards, occupational health and safety, employee job satisfaction, and termination of employment. The study employs a qualitative method with a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. Data analysis techniques involve categorizing audit findings based on elements of condition, criteria, cause, and effect. The results indicate that HR planning, selection and placement, career planning and development, and termination of employment are not yet operating economically, efficiently, and effectively. HR recruitment, training and development, performance evaluation, compensation and rewards, occupational health and safety, and employee job satisfaction are functioning economically, efficiently, and effectively.